REVOLUTIONIZING SOCIAL MEDIA MARKETING THROUGH AI AND AUTOMATION: AN IN-DEPTH ANALYSIS OF STRATEGIES, ETHICS, AND FUTURE TRENDS - Doby Indrawan; Yorman; Muhamad Stiadi; Nenden Hendayani; Al-Amin (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2023)
This comprehensive analysis delved into the transformative potential of artificial intelligence (AI) and automation in social media marketing. We explored many strategies and insights that have redefined how businesses engage with their audiences in the digital age. Our investigation began by acknowledging the profound impact of AI and automation technologies on the marketing landscape, particularly within the dynamic domain of social media. These innovations ushered in a new era of data-driven decision-making, hyper-personalization, and efficiency, enabling marketers to create more targeted and impactful campaigns. A key finding of our analysis was the pivotal role of AI in audience segmentation and targeting. Through real-time data analysis, marketers could identify and engage their ideal audience segments with exceptional precision, optimizing resource allocation and campaign effectiveness. We also highlighted the emergence of AI-driven chatbots and virtual assistants, revolutionizing customer service and engagement on social media platforms. These 24/7 available, personalized interaction tools significantly enhanced the overall customer experience. However, amidst the transformative potential of AI and automation, we emphasized the ethical responsibilities accompanying these advancements. We stressed the need for transparency, data privacy, and fairness in AI-driven marketing practices. Upholding these principles ensures trust, a cornerstone of long-term success. In conclusion, our analysis illuminated the remarkable potential of AI and automation in revolutionizing social media marketing. As we move forward into this era of technological transformation, we must do so with a steadfast commitment to innovation and ethical integrity, shaping a marketing landscape that benefits businesses and consumers alike.